Study of the association between rear-foot varus and patellofemoral pain - Venturini, Claudia; Morato, Flávio; Michetti, Henrique; Russo, Mayra; Carvalho, Vanice de Paula (Acta Fisiátrica, 2006)
Patellofemoral pain, also called anterior knee pain, is present in 25% of the population with 36% of them being adolescents, and with a higher prevalence among females and athletes. Objective: To assess the association between the presence of rear-foot varus, from the subtalar neutral position, and patellofemoral pain. Methods: Ten volunteers with unilateral or bilateral patellofemoral pain were assessed. The volunteers were submitted to the evaluation of rear-foot alignment from the subtalar neutral position. In order to do so, the volunteers were positioned in the ventral decubitus position, with the foot hanging parallel to the table. The angles formed by the straight lines that divide the legs and the calcanei were measured through a universal goniometer. Fisher test was used to assess the association between patellofemoral pain and rear-foot varus ≥ or < 8o. Results: The results of this study showed that all limbs with rear-foot varus > 8o (75%) presented pain, totaling 15 knees. Of the knees that presented rear-foot varus ≤ 8,2 (10%) presented pain and 3 (15%) did not. A statistically significant association between the degree of rear-foot varus and pain was demonstrated (p= 0.009). Discussion: Rear-foot varus causes an excessive pronation of the subtalar joint associated to the internal rotation of the tibia, with a consequent alignment alteration of the lower limb and patellofemoral pain. Conclusion: The results of this study suggest that there is an association between the presence of rear-foot varus and patellofemoral pain.